Assessing The Impact of Iron Smelting and Smithing on Social Economic Development of Indigenous People in Buhara Sub-County Kabale District. - Turinawe, Ronald (Kabale University, 2024)
Mineral developments especially iron smelting and smithing have contributed greatly to Buhara's economic and social development. Many challenges remain, however, including environmental pollution and resource waste in practice, as well as a dearth of systematic theoretical research. The goal of this study is to analyze the economic and social effects of iron smelting and smithing developments in Buhara from diversified perspectives, to provide the basis for the formulation of iron smelting and smithing development policy. The study aimed to assess the impact of iron smelting and smithing on the social and economic development of indigenous people.